DIFFERENT STABILITY OF RNA SECONDARY AND TERTIARY STRUCTURES - Mamasakhlisov, Ye. Sh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
The goal of this article is to clarify contribution of the chain entropy in stability of RNA secondary and tertiary structures. The Hamiltonian of the model includes relevant interactions explicitly. We show that different stability of secondary and tertiary structures governed by chain entropy rather than energy of interaction.
Keywords: RNA; folding; entropy